A Simple Zinc Catalyst for Carbamate Synthesis Directly from CO2. Issue 7 (3rd March 2017) - Zhang, Qiao; Yuan, Hao‐Yu; Fukaya, Norihisa; Yasuda, Hiroyuki; Choi, Jun‐Chul
Abstract: Several zinc salts were employed as catalysts for the synthesis of carbamates directly from aromatic amines, CO2, and silicate esters. Zn(OAc)2 offered the best performance among the salts tested. The addition of an N‐donor ligand such as 1, 10‐phenanthroline increased the yield. The best catalytic performance of Zn(OAc)2 can be explained by carboxylate‐assisted proton activation. The interaction between the substrate and the catalyst can be observed by chemical shifts in 1 H and 15 N NMR spectra. Isocyanate was a key intermediate, which was generated from amine and CO2 . Silicate ester was finally converted to siloxane, which was determined by 29 Si NMR. The commercially available catalyst system could be reused. The yield of isolated carbamate could reach up to 96 % with various substrates, and the catalytic reaction was amine‐selective in the presence of other functional groups. Abstract : Zinc rocks : A new method for synthesizing carbamates directly from amines and CO2 was developed. A commercially available zinc compound was used as the catalyst, and the addition of an N‐donor ligand increased the yield to 96 % (isolated product). Both aliphatic and aromatic amines could be activated, and thus the utility of this reaction in organic synthesis and the polyurethane industry is broad.